Emerging Trends in Sustainability Practices Within the FMCG Sector for A Better Future (International Journal of Scientific Research in Science and Technology, 2024)
The Fast-Moving Consumer Goods (FMCG) sector is undergoing a major transformation driven by increasing demands for sustainability. This article explores emerging sustainability trends, such as sustainable packaging, circular economy models, supply chain transparency, consumer engagement, and innovative product development. These practices not only mitigate environmental impact but also enhance business competitiveness and brand loyalty. By highlighting how leading FMCG companies are incorporating these trends, the article aims to inspire broader adoption of sustainable strategies that benefit both businesses and the environment.
Keywords: FMCG Sector; Sustainability; Sustainable Packaging; Circular Economy; Supply Chain Transparency; Consumer Engagement; Innovative Products; Environmental Impact; Eco-Conscious Consumers